TINDAK TUTUR PERLOKUSI PADA DIALOG FILM KELUARGA CEMARA KARYA YANDY LAURENS - Zulfa Naurah Nadzifah; Asep Purwo Yudi Utomo (Jurnal Komposisi, 2020)
This study describes the speech acts of perlocution in the film Kaluarga Cemara by Yandy Laurens, and then relates them to the context of the speech being pronounced. The research has two problems first, how the speech acts of smokings are used in the dialogue of the film Family Cemara by Yandy Laurens and second, how is the context or background of speech acts of speech found in the dialogues of the film Family of Cemara by Yandy Laurens. This research is a qualitative descriptive study, a research that describes and explains data coherently. The technique of providing data in this study uses the note taking technique, which is carried out by recording the data being examined. The note taking technique was carried out to record data in the form of utterances in the dialogue of the film Cemara Family by Yandy Laurens which contained speech acts of perlokusi. While the data analysis method uses the matching method. This method is used to match the form of speech acts of perlokusi with the conditions or context that surrounds them. The data source in this study is a sentence or dialogue which is a speech act of percocution contained in the dialogue of the film Cemara Family by Yandy Laurens. The results obtained show that there are nine forms of speech acts of perlokusi with each different purpose. Some aim to provide confirmation of a number of 2, question 2, statement 3, offer 1, and request 1. Actions that occur when it occurs are not separate from the situation that gave birth to the speech. Context can arise due to the topic of the speaker, the big problem that surrounds the condition of the speaker, the attitude of the speaker over past events, the desire for past conditions, the knowledge possessed by a speech purpose, to the desire to help the interlocutor.